Befall der Imagines von Aphthona euphorbiae Schrk. und Longitarsus parvulus Payk. durch Entomophthora sp. (Coleoptera: Halticidae; Entomophthoraceae). - Fritzsche, Rolf; Hoffmann, Günter-Martin (Contributions to Entomology = Beiträge zur Entomologie, 1959)
In spring 1958 the flax flea beetles Aphthona euphorbiae Schrk. and Longitarsus parvulus Payk. were found heavy infested by Entomophthora spec., especially after rainy days and high temperatures. The lower population density as like as the decrease of damages caused by young beetles as compared with the preceding year is traced back to the Entomophthora infestation of the old beetles and their reduced oviposition.